Case Report: Application of Mixed Reality Combined With A Surgical Template for Precise Periapical Surgery - Jia, Tingting; Qiao, Bo; Ren, Yipeng; Xing, Lejun; Ding, Baichen; Yuan, Fang; Luo, Qiang; Li, Hongbo (Frontiers in Surgery, 2022)
Objective The etiology of apical diseases is diverse, and most are due to incomplete root canal therapy. The common clinical manifestations include gingival abscess, fistula and bone destruction. The currently existing limitation of procedures is that surgeons cannot visually evaluate the surgical areas. We sought to combine mixed reality (MR) technology with a 3-dimensional (3D) printed surgical template to achieve visualization in apical surgery. Notably, no reports have described this application. Methods We created visual 3D (V3D) files and transferred them into the HoloLens system. We explained the surgical therapy plan to the patient using a mixed reality head-mounted display (MR-HMD). Then, the 3D information was preliminarily matched with the operative area, and the optimal surgical approach was determined by combining this information with 3D surgical guide plate technology. Results We successfully developed a suitable surgical workflow and confirmed the optimal surgical approach from the buccal side. We completely exposed the apical lesion and removed the inflammatory granulation tissue. Conclusion We are the first group to use the MR technique in apical surgery. We integrated the MR technique with a 3D surgical template to successfully accomplish the surgery. Desirable outcomes using minimally invasive therapy could be achieved with the MR technique.